CD11C immunopositive cells in the human fetal vermiform appendix - Radenković, Goran; Petrović, Vladimir; Nedin Ranković, Gorana; Denčić, Tijana; Živković, Vladimir; Jocić, Miodrag (Vojnosanitetski pregled, 2021)
Introduction/Aim. A vermiform appendix is an abdominal organ which contains the elements of gut-associated lymphoid tissue and carries out important immunological functions as a reservoir of intestinal microbial flora. It also has a role in the normal development of gut-associated lymphatic tissue. The aim of this study was to examine the distribution of dendritic cell marker CD11c in the human fetal vermiform appendix from the 13th to the 23rd week of development. Methods. The material in this study consisted of 28 human fetal vermiform appendixes from the 13th to the 23rd week of gestagion. The tissue samples were routinely processed to obtain paraffin blocks, and 5 µm thick tissue sections were stained with hematoxylin and eosin, and with rabbit monoclonal antibody against CD11c antigen and mouse monoclonal antibody against desmin. Results. The first CD11c immunopositive cells appear in the 14th week of development. They are present in the mucosa/submucosa and are interconnected via their cytoplasmic processes. Around these cells, a small number of lymphocytes can be seen. The first lymphoid aggregations appear in the 16th week of development, and lymphocytes are organized around the network made of CD11c immunopositive cells. From the 18th week of development, the lymphoid aggregations are organized in the form of primary lymphoid follicles, containing an extensive network made of CD11c immunopositive cells. Conclusion. CD11c immunopositive cells appear first in the process of primary lymphoid follicle generation and have a role in forming a lattice which will serve as the basis for lymphocyte migration.